2010
DOI: 10.1089/neu.2009.1159
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Proton MR Spectroscopic Imaging of Mild-to-Moderate Traumatic Brain Injury and Correlation with Neuropsychological Deficits

Abstract: Changes in the distribution of the magnetic resonance (MR)-observable brain metabolites N-acetyl aspartate (NAA), total choline (Cho), and total creatine (Cre), following mild-to-moderate closed-head traumatic brain injury (mTBI) were evaluated using volumetric proton MR spectroscopic imaging (MRSI). Studies were carried out during the subacute time period following injury, and associations of metabolite indices with neuropsychological test (NPT) results were evaluated. Twenty-nine subjects with mTBI and Glasg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(165 citation statements)
references
References 56 publications
10
149
2
4
Order By: Relevance
“…These experimental results have recently been confirmed 32 and strongly corroborate the finding reported in the present study, indicating temporary decrease in NAA and Cr levels and no change in Cho levels in our cohort of athletes with postconcussive head injury. Other authors indicated that patients suffering from mTBI underwent transient increase in Cr levels in the white matter and no change in NAA levels, 28,29 in contrast to the results of the present and previous studies 16,26,27,33,34 and also to a conspicuous number of preclinical studies demonstrating temporary decrease in NAA 8,10,11,21 and Cr pool following mTBI. 31,32 To explain their results, these authors concluded that an increase in total Cr (Cr and CrP) levels in the white matter may support a larger pool of high-energy phosphates (CrP and ATP), helping to restore mTBI-induced alteration of cell homeostasis through upregulation of membrane pumps and other processes of cellular repair.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These experimental results have recently been confirmed 32 and strongly corroborate the finding reported in the present study, indicating temporary decrease in NAA and Cr levels and no change in Cho levels in our cohort of athletes with postconcussive head injury. Other authors indicated that patients suffering from mTBI underwent transient increase in Cr levels in the white matter and no change in NAA levels, 28,29 in contrast to the results of the present and previous studies 16,26,27,33,34 and also to a conspicuous number of preclinical studies demonstrating temporary decrease in NAA 8,10,11,21 and Cr pool following mTBI. 31,32 To explain their results, these authors concluded that an increase in total Cr (Cr and CrP) levels in the white matter may support a larger pool of high-energy phosphates (CrP and ATP), helping to restore mTBI-induced alteration of cell homeostasis through upregulation of membrane pumps and other processes of cellular repair.…”
Section: Discussioncontrasting
confidence: 75%
“…Recent data seem to indicate that the Cr-CrP system in the brain plays an important role in performing the translocation of newly synthesized ATP from the mitochondrial compartment to the cytoplasmic compartment 40 and that Cr may act as a neurotransmitter. 40,41 Therefore, the postulated increase in total Cr levels following mTBI reported elsewhere 28,29 does not seem to have the support of either preclinical 31,32 or clinical studies, 26,27,33,34 or have a valid biochemical explanation. Conversely, the decrease in total Cr levels observed in our group of athletes with concussive head injury may well be explained by the experimentally documented general depression of brain metabolism after mTBI and corresponding to the window of metabolic brain vulnerability.…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, other metabolites, such as myoinositol, 31 citrate, 2 phosphorylcholine, and lactate may also be applied for tumor margin delineation. 34 In addition, newly developed technologies, such as phosphorus MRS (P-MRS) 18,37 and whole-brain proton MRS, 11 may also contribute to the delineation of tumor margins in future surgery.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Previously, it was thought that Cr (the creatine: phosphocreatine [Cr:PCr] pool) is maintained at a constant level in the brain, and is therefore used in many studies as an internal reference standard. Although it is known that Cr levels can change in certain conditions, ratios continue to be useful for reporting and comparing serial measurements or data among institutions using similar acquisition techniques, and has the advantage that correction for partial volume signal intensity loss and signal intensity calibrations are not required (Govind et al, 2010). Quantitation of MR spectra to determine absolute metabolite concentrations, however, is being used more commonly.…”
Section: Perfusion Imagingmentioning
confidence: 99%